Prediction of the Social Impact of Islamic Family Law on Women's Empowerment in Indonesia and Saudi Arabia: Analysis of Islamic Feminism, Structuralism, and Legal Socialization - Wilnan Fatahillah; Ririh Krishnani; Teguh Luhuringbudi (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study focuses on the possible social impacts of Islamic family law on women's empowerment in Indonesia and Saudi Arabia, with the aim of exploring the interaction between Islamic feminist theory, Pierre Bourdieu's structuralism, and Lawrence Friedman's legal socialization theory. The data collection method was carried out through documentation analysis and in-depth literature study, covering primary sources such as family law laws and regulations. The data collected were analyzed using a qualitative approach that allows for the identification of patterns, themes, and trends that are relevant in predicting the implementation of the law in both countries. The findings show a significant difference between the normativity that describes legal practice and social reality, where legal norms are often not in line with the conditions faced by women in everyday life. The conclusion of this study emphasizes the need for more inclusive legal reforms and public education on women's rights as a step towards achieving better gender equality. The contribution of this study promises a novel aspect, namely the integration of different theories to gain a more comprehensive understanding. Several limitations were also found in the data collection that indicate the need for further research, especially involving women's perspectives and other socio-economic, religious, political, and educational factors in the context of family law. Suggestions for future research include exploring cross-national collaboration to broaden understanding of Islamic law and its impact on women's empowerment globally.